1954
DOI: 10.1002/jpln.19540660102
|View full text |Cite
|
Sign up to set email alerts
|

Weitere Untersuchungen über Beziehungen zwischen Nährstoffversorgung und Oxalsäurebildung im Zuckerrüben- und Mangoldblatt

Abstract: Die Actinomycine sind eine Gruppe von roten Antibiotica, deren Molekel aus einem Farbstoffteil und einer Reihe offenbar polypeptid‐artig verknüpfter Aminosäuren aufgebaut ist. Sie sind durch cytostatische und tumorhemmende Wirkung ausgezeichnet und zeigen Wirksamkeit gegen Lymphogranulomatose. Die bisher bei ihrer chemischen, biologischen und medizinischen Untersuchung erhaltenen Ergebnisse werden zusammenfassend dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1955
1955
1987
1987

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In a number of plant species, nitrate as the source of nitrogen as opposed to ammonium lead to a higher oxalate content of the plant (Clark, 1936;Gilbert et al, 1951;Scharrer and Jung, 1954;Grütz, 1956;Becker, 1964;Ehrendorfer, 1964a;Joy, 1964;Knauer and Simon, 1968;Kick and Massen, 1973;Kpodar et al, 1978). Some representative data are summarized in Table I.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In a number of plant species, nitrate as the source of nitrogen as opposed to ammonium lead to a higher oxalate content of the plant (Clark, 1936;Gilbert et al, 1951;Scharrer and Jung, 1954;Grütz, 1956;Becker, 1964;Ehrendorfer, 1964a;Joy, 1964;Knauer and Simon, 1968;Kick and Massen, 1973;Kpodar et al, 1978). Some representative data are summarized in Table I.…”
mentioning
confidence: 99%
“…A positive correlation between calcium content of the growth medium and oxalate formation (Olsen, 1939;Gilbert et al, 1951;Scharrer and Jung, 1954;Grütz, 1956;Rasmussen and Smith, 1961;Bornkamm, 1965;Zindler-Frank, 1975) appears to be related to processes involving chemical regulation: Uptake of calcium leads to calcium oxalate precipitation, altering the equilibrium of oxalate synthesis and/or breakdown in the plant. In some investigations on plants with a high level of water-soluble oxalates (Chenopodiaceae and Polygonaceae),.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to explain a physiological role of calcium oxalate and free oxalic acid, early investigators Amar (1904), Stuhl (1920), Muller (as cited by Zindler- Frank, 1975) thought of excess calcium uptake as harmful and the oxalate necessary to tie it up. Later studies (Olsen, 1939;Scharrer and Jung, 1954;Âckermann, 1958) for the induction of oxalate synthesis. In earlier studies, she found that the number of cells which differentiate into Idloblasts is dependent on the amount of nutritional calcium (Frank, 1972) and that inhibition of glycolate oxidase decreases the number of idloblasts (Zindler- Frank, 1974).…”
Section: Oxalic Acidmentioning
confidence: 99%